Tindak Pidana terhadap Pelaku Penanaman Pohon Ganja Secara Ilegal Berdasarkan Putusan Pengadilan Negeri Sanggau Nomor 111/Pid.Sus/2017/Pn.Sag - Gaviota Adrian Yohan; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2022)
Narcotics are substances or drugs derived from a plant, either synthetic or semi-synthetic, which can cause a decrease or change in consciousness, relieve pain, and even cause dependence, one of which is marijuana. Cannabis is prohibited from being used for the benefit of health services. The purpose of this research was to analyze the regulation of criminal acts for perpetrators of illegally planting marijuana trees and to discuss the considerations of the panel of judges against perpetrators of illegally planting marijuana trees for medicinal purposes. The normative method is used in conducting this research, which uses the Legislative approach, and the conceptual approach. Sources of legal materials consist of primary and secondary sources. Data collection techniques using library techniques and note-taking techniques. The results of the research indicate that someone planting marijuana trees without rights is an unlawful act and the act of planting marijuana exceeds five trees, the perpetrators are charged with Article 111 paragraphs (1) and (2) of the Narcotics Law and the judge's consideration in deciding cases based on article 116 paragraph (1) of the Narcotics Law.